2021
DOI: 10.1111/rda.14063
|View full text |Cite
|
Sign up to set email alerts
|

Effects of individual or in‐combination antioxidant supplementation during in vitro maturation culture on the developmental competence and quality of porcine embryos

Abstract: The oocyte maturation process requires a high supply of energy, which generates reactive oxygen species (ROS), adversely affecting oocyte and embryo development.Balancing ROS by antioxidant supplementation is essential for maintaining oocyte maturation and embryonic quality in vitro. This study aimed to evaluate the impact of four antioxidants: β-mercaptoethanol (β-ME), chlorogenic acid (CGA), curcumin and sericin, when applied individually or in combinations, during oocyte maturation on development of porcine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
(54 reference statements)
0
4
0
Order By: Relevance
“…Furthermore, for the aforementioned reasons, the desirable OA‐mediated impacts might be reflected in the enhancements of ex vivo developmental potential, molecular quality, mitochondrial functions and incidence of genomic DNA‐inherited genes to undergo reprogramming of their transcriptional activities in porcine and other mammalian in vitro‐produced embryos that have been created using a variety of advanced assisted reproductive technologies (ARTs). Among those ARTs, special importance should be assigned to in vitro fertilization (IVF) by standard gamete co‐incubation or intracytoplasmic sperm injection (Arraztoa et al, 2017; Casillas et al, 2018; Kagawa et al, 2022; Thongkittidilok et al, 2022) and cloning by somatic cell nuclear transfer (Deng et al, 2020; Gorczyca et al, 2021; Jeong et al, 2021; Wiater et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, for the aforementioned reasons, the desirable OA‐mediated impacts might be reflected in the enhancements of ex vivo developmental potential, molecular quality, mitochondrial functions and incidence of genomic DNA‐inherited genes to undergo reprogramming of their transcriptional activities in porcine and other mammalian in vitro‐produced embryos that have been created using a variety of advanced assisted reproductive technologies (ARTs). Among those ARTs, special importance should be assigned to in vitro fertilization (IVF) by standard gamete co‐incubation or intracytoplasmic sperm injection (Arraztoa et al, 2017; Casillas et al, 2018; Kagawa et al, 2022; Thongkittidilok et al, 2022) and cloning by somatic cell nuclear transfer (Deng et al, 2020; Gorczyca et al, 2021; Jeong et al, 2021; Wiater et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…But this negative effect might be relieved by supplementing AXE during IVM of pig COCs. Furthermore, providing a mechanistic insight into the biological scenario, by which AXE‐dependent resilience of in vitro‐maturing pig COCs to PA triggered processes of oxidative stress and apoptosis is prompted, might bring about not only amelioration of developmental capabilities but also improvement of molecular quality of porcine and other mammalian embryos generated by such assisted reproductive technologies as standard or intracytoplasmic sperm injection (ICSI)‐mediated in vitro fertilization (Douet et al, 2017; Hara et al, 2011; Jin et al, 2009; Thongkittidilok et al, 2022) and somatic cell nuclear transfer (SCNT)‐based cloning (Ren et al, 2014; Samiec & Skrzyszowska, 2005, 2013; Skrzyszowska et al, 2006a; Wiater et al, 2021; Zhong et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, the maturation of pig oocytes might be hin- (Douet et al, 2017;Hara et al, 2011;Jin et al, 2009;Thongkittidilok et al, 2022) and somatic cell nuclear transfer (SCNT)-based cloning (Ren et al, 2014;Samiec & Skrzyszowska, 2005Skrzyszowska et al, 2006a;Wiater et al, 2021;Zhong et al, 2008).…”
Section: F I G U R Ementioning
confidence: 99%
“…In addition, the addition of CGA during in vitro maturation culture could significantly increase the rate of oocyte development into blastocysts and reduce the apoptotic nuclear index, thereby improving the quality of pig embryo development and electroporation-treated embryos (Nguyen et al, 2018). In addition, supplementation with CGA-containing antioxidants during maturation may enhance blastocyst formation and improve blastocyst quality (Thongkittidilok et al, 2022). Nguyen, Hirata, et al (2019) found that the addition of 50 μM CGA to the storage medium increased the blastocyst formation rate of post-storage porcine fertilized eggs.…”
Section: Effect Of Cga On Meat Qualitymentioning
confidence: 99%